Advancing Sustainable Marine Transportation: Offshore Floating Electric Vessel Charging Stations - Sruthy V; Preetha P K (International Journal of Sustainable Energy Planning and Management)
The feasibility analysis of offshore floating charging stations (FCS) incorporating renewable energy sources (RES) in India and around the world presents a promising and pioneering solution to meet the emerging demands of maritime transport systems for sustainable development. The global shift towards sustainable transportation supports the increasing adoption of electric vessels (E-vessel), which forces the inclusion of innovative solutions for their reliable operation. This study includes a feasibility analysis of FCS combined with an energy management system for reliable operation. A real-time analysis was conducted at an offshore location in the Arabian Sea, near Gujrat, India, to assess the operational and implementation possibilities of FCSs in India, especially in the Exclusive Economic Zone (EEZ). An appropriate energy management system in the FCS tackles E-vessel demand changes, real-time variations in RES, and energy flow balance with reduced reliance on backup energy systems. The findings demonstrated a reduction of 70.2% in the backup energy requirement for the FCS, and the energy management system ensured that the FCS had an immense improvement in excess RES support to meet additional E-vessel demands. This paper also included a comparative analysis between an offshore location in India and one in Europe. This study underscores the potential of FCS to enhance the adoption of E-vessels in India’s and global marine transportation.